Understanding the impact of amyloid beta targeted therapies on biomarkers and clinical endpoints in Alzheimer's disease - Petersen, Ronald C.; Graf, Ana; Atkins, Alexandra S.; Brys, Miroslaw; Murphy, Jennifer; Miller, David S.; Reyderman, Larisa; Siemers, Eric; Smith, Janice; Carrillo, Maria C.; Weber, Christopher J. (Alzheimer's & dementia : translational research & clinical interventions, 2025)
The Alzheimer's disease (AD) scientific field continues to make significant advances in early detection and treatments, which importantly rest on advances in our fundamental understanding of AD pathobiology and its contribution to cognitive decline. Clinical readouts of monoclonal antibodies against various forms of the amyloid beta (Aβ) protein indicate that the impact of these treatments may extend beyond reduction in amyloid plaques. The Alzheimer's Association Research Roundtable meeting held on May 17 and 18, 2022, reviewed our understanding to date of the impact of treatments targeting various species of Aβ; its impact on other related pathophysiology including tau; and ultimately, its effects on neurodegeneration and clinical decline, driven by the latest available data. Participants discussed the current evidence for a causal relationship among amyloid accumulation, tau alteration, and cognitive decline; the effect of anti‐amyloid therapies on clinical and biomarker endpoints; and how we can accelerate the pathway to therapeutic approval and what should guide us for the near future. Highlights The Alzheimer's Association Research Roundtable convened leaders from industry and academia, as well as patients, clinicians, and government and regulatory agency scientists to discuss the topic “Current Understanding of AD Pathophysiology & Impact of Amyloid‐beta Targeted Treatments on Biomarkers and Clinical Endpoints.” The totality of scientific evidence (clinical trials, animal data, modeling, and observational studies) on the relationship between amyloid beta (Aβ), amyloid, tau, and cognitive impairment is helping our understanding of the downstream effects and overall importance of lowering amyloid plaque load. Based on data from multiple phase 2 and 3 clinical trials of anti‐amyloid monoclonal antibodies, there is strong evidence to support that a sufficiently large reduction in amyloid plaque load to near‐normal levels is associated with positive changes in tau biomarkers and clinical endpoints. Reduction of Aβ plaque, measured easily by plasma amyloid biomarkers, is reasonably likely to predict benefit in clinical outcome measures.